Allelic frequencies and association with carcass traits of six genes in local subpopulations of Japanese Black cattle. (7th August 2015) - Nishimaki, Takahiro; Ibi, Takayuki; Siqintuya,; Kobayashi, Naohiko; Matsuhashi, Tamako; Akiyama, Takayuki; Yoshida, Emi; Imai, Kazumi; Matsui, Mayu; Uemura, Keiichi; Eto, Hisayoshi; Watanabe, Naoto; et al.
Abstract: Marker‐assisted selection (MAS) is expected to accelerate the genetic improvement of Japanese Black cattle. However, verification of the effects of the genes for MAS in different subpopulations is required prior to the application of MAS. In this study, we investigated the allelic frequencies and genotypic effects for carcass traits of six genes, which can be used in MAS, in eight local subpopulations. These genes are SCD, FASN and SREBP1, which are associated with the fatty acid composition of meat, and NCAPG, MC1R and F11, which are associated with carcass weight, coat color and blood coagulation abnormality, respectively. The frequencies of desirable alleles of SCD and FASN were relatively high and that of NCAPG was relatively low, and NCAPG was significantly associated with several carcass traits, including carcass weight. The proportions of genotypic variance explained by NCAPG to phenotypic variance were 4.83 for carcass weight. We thus confirmed that NCAPG is a useful marker for selection of carcass traits in these subpopulations. In addition, we found that the desirable alleles of six genes showed no negative effects on carcass traits. Therefore, selection using these genes to improve target traits should not have negative impacts on carcass traits.